Comparative Study of the Implementation of Pesantren Kilat and Mabit at the Mosque in Gema Ramadhan Activities from a Fiqh Perspective - Kyla Jessica Veda; Hasna Raissa; Qodim Ma’shum (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the concepts and characteristics of Islamic short-term boarding programs (pesantren kilat) and overnight spiritual programs (mabit) within the Gema Ramadhan activities in mosques, examine their implementation from an Islamic jurisprudence (fiqh) perspective, and compare their implications for the development of students’ religious character. This research employs a qualitative approach with a field research design and a comparative study method, conducted at Al Ittihad Mosque in Sanggung Village and TPQ Ar-Ridha in Wunut Village. The research subjects were selected using purposive sampling, including program organizers and facilitators. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. The findings indicate that pesantren kilat emphasizes cognitive development through structured learning, while mabit focuses on strengthening spiritual aspects through direct worship experiences. From a fiqh perspective, both activities are permissible as forms of mosque prosperity (i‘mar al-masjid), provided they maintain proper etiquette, cleanliness, order, and do not interfere with the mosque’s primary function as a place of worship. Mabit demonstrates a higher level of conformity with the mosque’s function due to its dominance of ritual worship (ibadah mahdhah), whereas pesantren kilat falls under non-ritual worship (ibadah ghairu mahdhah) with conditional permissibility. Comparatively, both are complementary in fostering religious character by integrating cognitive, affective, and spiritual dimensions in a balanced manner.